BSL-4 for High Risk Animal Pathogens in India - Kulkarni, Diwakar D (Indian Farming, 2015)
Due to the long untiring efforts of some visionaries, the BSL-4Biocontainment Lab was established in Bhopal, the first of its kind inIndia to work on exotic diseases of animals.